DEVELOPMENT AND VALIDATION OF A STABILITY INDICATING REVERSE PHASEHIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS DETERMINATION OF CLINDAMYCIN, METRONIDAZOLE, AND CLOTRIMAZOLE IN PHARMACEUTICAL COMBINED DOSAGE FORMS - Ponnuri, Revathi Naga Lakshmi; Pragallapati, Prahlad; Sk, Mastanamma; N, Ravindra; Mandava, Venkata Basaveswara Rao; Sudha, Borusu Sri Naga; Prasad, Koppisetti Baladurga (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of present work was to develop and validate a simple, fast, precise, selective, and accurate reverse phase high-performance liquid chromatography method for the simultaneous determination of Clindamycine, Metronidazole and Clotrimazole in a pharmaceutical dosage form. Methods: The separation of these three drugs was achieved on ODS 250Ã—4.6 mm, 5 mm C18 column. Mobile phase containing 0.1% ortho phosphoric acid buffer and acetonitrile in the ratio of 55:45 v/v was pumped through column at a flow rate of 1 ml/minute. Temperature was maintained at 30Â°C and ultraviolet detection at 238 nm. Results: The retention times were observed to be 2.591, 3.584, and 4.221 minutes for Clindamycine, Metronidazole, and Clotrimazole, respectively. Linearity was found to be 25-150 Î¼g/ml Clindamycine, Metronidazole, and Clotrimazole, respectively. The method was statistically validated for linearity, recovery, the limit of detection (LOD), limit of quantification (LOQ), accuracy, and precision. The stress testing of the drugs individually and their mixture are carried out under acidic, alkaline, oxidation, photostability, and thermal degradation conditions and its degradation products are well resolved from the analyte peaks. Conclusion: This method was successfully validated for accuracy, precision, and linearity, LOD, and LOQ. Keywords: Clindamycine, Metronidazole, Clotrimazole, Reverse phase-high performance liquid chromatography, Simultaneous determination, Degradation studies.